Inquiry Learning Model in Chemistry Education: A Systematic Literature Review - Purwandari, Intan Diah; Rahayu, Sri; Dasna, I Wayan (FKIP Universitas Lampung, 2022)
Currently in the 21st century, students are required to master various abilities and thinking skills. Students' abilities do not develop well with learning that only focuses on convergent thinking training. As a result, students have difficulty in developing and improving their ability to master the learning material. Therefore, it is necessary to have an appropriate learning model to improve students' abilities. Based on this, one of the alternative learning models that can improve students' abilities is the Inquiry Learning model. This article aims to provide an overview of the application of the Inquiry Learning model to the achievement of learning objectives in chemistry so that it can improve students' abilities. The method used is a systematic literature review from a literature review with relevant and reputable sources during the period 2017 to 2021. The results show that the inquiry learning model was able to improve students' ability to learn chemistry. Keywords: chemistry, critical thinking, inquiry learning model. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp681-691